The steatosis‐associated fibrosis estimator score is a useful indicator of recurrence and survival after initial curative hepatectomy for hepatocellular carcinoma - Tomoaki Bekki; Masahiro Ohira; Yuki Imaoka; Minoru Hattori; Ryosuke Nakano; Hiroshi Sakai; Shintaro Kuroda; Hiroyuki Tahara; Kentaro Ide; Tsuyoshi Kobayashi; Hideki Ohdan (Annals of Gastroenterological Surgery)
Abstract Aims Liver fibrosis predisposes patients to liver failure and hepatocellular carcinoma. Various markers, which can be calculated easily from serum parameters, have been reported to predict liver fibrosis accurately. This study investigated the prognostic factors, including blood‐based markers for liver fibrosis of patients with hepatocellular carcinoma following initial curative hepatectomy. Methods This retrospective study included 407 patients with hepatocellular carcinoma who underwent initial curative hepatectomy between April 2010 and December 2017. We investigated prognosis‐associated variables in these patients. Results Among the blood‐based markers for liver fibrosis examined in this study, the steatosis‐associated fibrosis estimator score demonstrated the best predictive capabilities. This score was revealed as a poor prognostic factor for both overall survival and recurrence‐free survival in patients with hepatocellular carcinoma following initial curative hepatectomy. A high steatosis‐associated fibrosis estimator score was independently associated with poor overall survival and recurrence‐free survival. After propensity score‐matching to minimize bias between high‐ and low‐steatosis‐associated fibrosis estimator score groups, the high steatosis‐associated fibrosis estimator score remained associated with poor overall survival and recurrence‐free survival. Conclusions The steatosis‐associated fibrosis estimator score is an independent predictor of long‐term prognosis in patients with hepatocellular carcinoma following initial curative hepatectomy.